Yield of aromatics from naphthenics upon catalytic cracking - Pujro Tarquino, Richard Alfonzo (2012)
Cis- and trans-decalin were reacted over cracking catalysts to study the formation of aromatics in a particular fraction of the liquid products obtained in the fluid catalytic cracking process (FCC). A batch, fluidized bed CREC riser simulator reactor was used at 673 and 723 K and contact times varied from 3 to 15 s. Cis-decalin was much more reactive. Despite differences induced and measured in their accessibility indices, the catalysts led to similar activity profiles, suggesting that diffusion restrictions do not prevail. Products were C 1 -C 12 hydrocarbons while coke was very low. Isomerization, cracking, hydrogen transfer, ring opening, ring contraction and alkylation reactions occurred and products from the various reactions were observed at very short reaction times. Bicyclic C 10 naphthenics and alkyl-substituted C 7 -C 11 aromatics or naphtheno-aromatics were the most important products. A reaction mechanism with three initial routes (isomerization, ring opening and direct hydrogen transfer reactions) was proposed.